Hybrid Approach of Handwritten Malayalam Character Recognition - James, Ajay; Varghese K, Sonu; Saravanan, Chandran (International Journal of Engineering and Technology, 2018)
Handwritten character recognition of South Indian scripts especially Malayalam is an on-going area of research. Limited works are proposed in this field due to the significant character set with highly complex and similar characters. Here hybrid technique of feature extraction based on geometrical and structural properties of characters is proposed. This method consists of two stages, in the first stage characters areclassified into a group based on geometrical features such as the number of ending, bifurcation and loop. And in the second stage characters are recognized based on specific characteristics defined for each group. The proposed method exhibits recognition rate of 96.5% and accuracy of 93.86% on an average.